Pengaruh Suku Bunga, Imbal Hasil Sukuk Dan Produk Domestik Bruto (PDB) Terhadap Permintaan Sukuk Di Indonesia - Nurmalasari Nurmalasari; Sri Dewi Ayu Safitri; Mohammad Kamal Reza (LPPM Universitas BSI, 2023)
community related to the importance of investment one of which is sukuk. Sukuk is one of the investment instruments that provide opportunities for Muslim and non-Muslim investors to start investing in Indonesia. Macroeconomic variables can reflect a country's economic stability. The purpose of this study is to find out the influence of interest rates, sukuk yields and GDP on sukuk demand in Indonesia. Data analysis is done using multiple linear regression methods, using the smallest square (ordinary leas Square). Data processing using SPSS 25.0. From the results of the research that the first hypothesis proposed is the variable Deposit Rate statistically. Judging from the regression coefficient which is worth 0.854 (Positive). So the value of the statement in the first hypothesis is supported in this study. The second hypothesis proposed is the Sukuk Yield variable that sukuk yield has a positive influence on sukuk demand and the third hypothesis proposed is that GDP results positively on sukuk demand in Indonesia.Keywords : Interest rates, sukuk yields, gross domestic product, sukuk.Â community related to the importance of investment one of which is sukuk. Sukuk is one of the investment instruments that provide opportunities for Muslim and non-Muslim investors to start investing in Indonesia. Macroeconomic variables can reflect a country's economic stability. The purpose of this study is to find out the influence of interest rates, sukuk yields and GDP on sukuk demand in Indonesia. Data analysis is done using multiple linear regression methods, using the smallest square (ordinary leas Square). Data processing using SPSS 25.0. From the results of the research that the first hypothesis proposed is the variable Deposit Rate statistically. Judging from the regression coefficient which is worth 0.854 (Positive). So the value of the statement in the first hypothesis is supported in this study. The second hypothesis proposed is the Sukuk Yield variable that sukuk yield has a positive influence on sukuk demand and the third hypothesis proposed is that GDP results positively on sukuk demand in Indonesia.Keywords : Interest rates, sukuk yields, gross domestic product, sukuk. Â